Social Support as a Mediator Between Cyberbullying Victimization and Psychological Distress in Adolescents - Acar, Zeynep; Al-Taie, Zainab (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2025)
Objective: This study aimed to investigate the mediating role of social support in the relationship between cyberbullying victimization and psychological distress among adolescents in Iraq.Methods and Materials: A descriptive correlational research design was employed with a sample of 395 adolescents selected based on the Krejcie and Morgan sampling table. Participants were recruited from various high schools in Iraq using stratified random sampling. Standardized tools were utilized to measure cyberbullying victimization (Cyberbullying and Online Aggression Survey Instrument), social support (Multidimensional Scale of Perceived Social Support), and psychological distress (Kessler Psychological Distress Scale, K10). Data were analyzed using SPSS version 27 and AMOS version 21. Pearson correlation coefficients were computed to examine bivariate relationships, and Structural Equation Modeling (SEM) was performed to test the mediation model and model fit.Findings: Results showed that cyberbullying victimization was positively associated with psychological distress (r = .53, p < .001), while social support was negatively associated with both cyberbullying (r = −.41, p < .001) and psychological distress (r = −.46, p < .001). The SEM analysis revealed good model fit (χ²/df = 2.08, CFI = 0.97, RMSEA = 0.052) and supported partial mediation. Cyberbullying had a significant direct effect on psychological distress (B = 0.43, β = 0.38, p < .001), while social support significantly mediated this relationship (indirect effect = −0.19, p < .001).Conclusion: These findings underscore the critical role of perceived social support in mitigating the psychological consequences of cyberbullying victimization among adolescents. Promoting supportive social environments within families, peer groups, and schools may serve as a protective factor against mental health issues in digitally active youth populations.